Necesidad de armonizar el art. 370, numeral 3, del código de la niñez y adolescencia del ecuador, con relación a la ejecutabilidad de los sucesos tipificados como infracción penal en los adolescentes - Quevedo Torres, Angélica Patricia (2017)
The research entitled "THE NEED TO HARMONIZE ART. 370, PARAGRAPH 3 CODE OF CHILDHOOD AND ADOLESCENCE OF ECUADOR, WITH RESPECT TO THE ENFORCEMENT OF TYPED EVENTS AS CRIMINAL OFFENSE IN TEENAGERS" I want to conduct the study on the need in our country to create laws that prevent adolescents from being involved in crimes against life. The problem stems from the originating detected problematic because the absence of severe sanctions in the law to suppress criminal acts of juvenile offenders and their reintegration because not met as required by the Constitution of the Republic. This causes serious problems arising to society in general, as it does not allow fully complies with certain constitutional rights in the Act. Establishing that it is a major and important issue that deserves an analytical research, and critical about the reality of our country, and because it is a social legal problem deserves to be treated as an objective of the research study. In others we are concerned not only in the professional field but also as a society, we must be aware and know how is aimed at the implementation of the law as far as juvenile offenders are concerned. For the problem lies in the implementation of socio-educational measures, because in reality these do not fulfill their function, which were created, and because these measures in institutional placement are not very severe, this causes the rights of victims to be violated. There violation of the rights of victims when their attackers for being offenders which adolescents; murder, rob, rape and trafficking are not punished with stringent laws to placate juvenile delinquency that exists in the country, wreaking havoc in Ecuadorian society, as this leads to recidivism other criminal acts. The victim is not satisfied with the punishment imposed on juvenile offenders, victims also have rights that must be respected, where should prevail equity rights. This is why it is essential to conduct this research in which a detailed analysis is set to reform regarding cases of adolescents in ordinary legislation are punishable by imprisonment for the commission of crimes such as murder, trafficking drugs, rape, aggravated robbery with a weapon, kidnapping with death; crimes that disrupts the social peace.